PENGARUH MEKANISME CORPORATE GOVERNANCE DAN MANAJEMEN LABA TERHADAP KINERJA KEUANGAN PERUSAHAAN YANG TERDAFTAR DI INDEKS LQ 45 - Fariz Maulana Ghazali (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2019)
Introduction: The objective of this research is to examine how to influence of corporate governance and earnings management on financial performance. Methods: Independent variables in this research are managerial ownership, institutional ownership, independent commissioners, audit committees and earnings management. Dependent variable is financial performance. Earnings management in this research was measured using Modified Jones Models, while financial performance was measured by cash flow return on assets (CFROA). Sampel was conducted on the company that listed at Indeks 45 Indonesia Stock Exchange. The sample period of this research is 2013. Data of this research are analyzed using multiple regression. Results: The results of the analysis show that managerial ownership, institutional ownership, independent commissioners and audit committees have not influence to financial performance. Earnings management have influence to financial performance.Conclusion and suggestion: Subsequent research can make comparisons between stock indices on the Indonesia Stock Exchange and the use of different models in determining corporate governance and discretionary accruals and extending the observation period so that there are mechanisms for corporate governance and earnings management with different points of view.